Determinants of Full Vaccination Coverage among Children Aged 12-23 Months in Bangladesh: A Comparison between High- and Low-Performing Divisions - Moriam Khanam; Nahid Akhter Jahan (Hindawi Limited, 2024)
Introduction. A better understanding of the significant factors behind childhood vaccination is important for designing strategies to increase vaccination coverage and reduce child mortality and morbidity. The study is aimed at identifying the determinants of full vaccination coverage among children aged 12-23 months in Bangladesh and at comparing the determinants between high- and low-performing areas. Methods. This study used the latest available Bangladesh Demographic and Health Survey 2017-18 data. A weighted sample of 1678 children was included in this study. The association between full vaccination coverage and explanatory variables was identified using chi-square test. Multivariable logistic regression analysis was employed to identify associated factors of full vaccination coverage. Results. Findings showed that about 88% of the children had full vaccination coverage. The odds of full vaccination coverage was significantly higher among children of mothers with secondary education compared to children of mothers with no formal education (AOR=2.07, 95%CI=1.16 to 3.70). Mother's working status was another significant factor behind full vaccination coverage (AOR=1.53, 95%CI=1.002 to 2.34). In addition, we identified that higher age of mother (AOR=2.76, 95%CI=1.28 to 5.96 for 20-34 years group and AOR=12.14, 95%CI=1.21 to 122.41 for 35 and above age group) and being in middle-income household (AOR=4.66, 95%CI=1.33 to 16.34) were significantly associated with full vaccination coverage in high-performing areas. On the other hand, children of mothers with secondary education level (AOR=2.31, 95%CI=1.86 to 4.49) and exposure to media (AOR=1.58, 95%CI=1.001 to 2.50) had higher odds of having full vaccination coverage in low-performing areas. Conclusions. This study identified the associated factors of full vaccination coverage among children. The findings indicate the importance of maternal education and mothers' employment for children's vaccination uptake. In low-performing areas, investment in education and awareness raising initiatives may play instrumental role in achieving full vaccination coverage.